Kemampuan Ekstrak Daun Kedondong (Spondias dulcis Forst.) Sebagai Larvasida Nabati terhadap Larva Instar III Culex quinquefasciatus - Mustafa Kamal; Galuh Okta Kristiani; Salni Salni (Faculty of Mathtmatics and Natural Sciences, 2018)
Culex quinquefasciatus mosquito control can be performed at the larval stage using more environmentally friendly leaf of Spondias dulcis Forst. This study aims to determine the ability of extracts contained in the leaf S. dulcis Fosrt. as larvacide to larvae Cx. quinquefasciatus instar III. The study used Completely Randomized Design (RAL) with 6 treatments repeated 4 times. The treatment used was 125 ppm, 250 ppm, 500 ppm, and 1000 ppm with 2 controls, ie 0 ppm and temefos 1 ppm. Observations were made after 24 hours of exposure and data obtained in the analysis using one way ANOVA, to see the real difference used Duncan test, and Probit was used to calculate the LC50 value. The results obtained are the extract has the ability as a larvacide of killing by 92.50% at a concentration of 1000 ppm.